0169 Simulation in acute medicine: A novel multi-disciplinary team training programme mapped to the UK core medical training curriculum. (2nd November 2015) - Thethy, Ishwinder; Butler, Laura; Ramsay, Hannah; Talbot, Harriet; Dover, Anna; McCallum, Lynn
Abstract : Background: Simulation-based medical education (SBME) is increasingly used in healthcare to improve training, quality of care and patient safety. 1 It facilitates learning in a supportive environment and encourages evaluation of practice within a multidisciplinary team (MDT). Although integration of SBME into the postgraduate curriculum is thought to be a key feature for its effective use, 2 there is a relative dearth in Acute Medicine. We have designed and implemented a multidisciplinary high-fidelity simulation program in Acute Medicine at the Royal Infirmary of Edinburgh (RIE), mapped to the CMT curriculum. 3 Our aim is to improve patient safety by simulating acute medical emergencies. Methodology: MDT based simulation sessions (comprising three scenarios) are delivered monthly by trained faculty members in the simulation suite at RIE. Twelve scenarios encompass the top 24 presentations in the CMT Curriculum, 3 with learning outcomes mapped to specified competencies. 3 Post session feedback questionnaires were developed to assess immediate benefit and long-term application of learning. Results: To date, four sessions have been attended by a total of 19 participants (comprising ANPs, Foundation and CMT doctors). All reported: Simulation within a team setting was realistic to practice and engendered better team working, leadership and communication. The sessions were applicable to their curricular needs and had positively influenced clinical care. Enthusiasm to attend further sessions, agreeing that they would highly recommend these to others and that simulation should be a mandatory part of training. Feedback from one of the sessions (after 8 weeks) shows that the learning outcomes have been applied to clinical practice in the long term with reported increased confidence in the management of the acutely unwell patient and improved teamwork. Potential impact: Provisional analysis suggests increased confidence in the management of acute medical emergencies and improved working within a MDT. Both of these outcomes facilitate patient safety. References: Aggarwal R, et al . Training and simulation for patient safety. Qual Saf Health Care 2010;19:34–43 Issenberg SB, et al . Features and uses of high-fidelity medical simulations that lead to effective learning: a BEME systematic review. Med Teach 27:10–28 Joint Royal Colleges of Physicians Training Board. Specialty Training Curriculum for Core Medical Training. August 2009 (with amendments August 2013). Available at: http://www.mrcpuk.org/sites/default/files/documents/2009-CMT-Curriculum-(Amended%20Aug%202013).pdf